2012
DOI: 10.1017/s002221511200196x
|View full text |Cite
|
Sign up to set email alerts
|

Guillotine versus dissection tonsillectomy: randomised, controlled trial

Abstract: Link to this article: http://journals.cambridge.org/abstract_S002221511200196XHow to cite this article: S J Frampton, M J A Ward, V S Sunkaraneni, H IsmailKoch, Z A Sheppard, R J Salib and P K Jain Guillotine versus dissection tonsillectomy: randomised, controlled trial. AbstractObjective: This trial aimed to compare the guillotine technique of tonsillectomy with 'cold steel' dissection, the current 'gold standard'.Design: A single centre, randomised, controlled trial. Methods: One hundred children aged 3 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 13 publications
(47 reference statements)
0
14
0
Order By: Relevance
“…PTH may have been reported as primary (generally defined as occurring within 24 hours of surgery), secondary (generally defined as occurring more than 24 hours postoperatively), or at an undefined or unspecified time. 8–108 Seventy-three studies contributed data to the meta-analysis (66 RCTs, 19,20,23,25,27,29,33,34,36,3841,43,44,46,47,49,50,5259,6264,67,71,72,7479,8184,88–92,95,101–105,108–122 6 nonrandomized trials, 24,35,37,45,48,94 and 1 prospective cohort study 70 ). The resulting subset of studies included the following tonsillectomy techniques: cold dissection, electrocautery, coblation, harmonic scalpel, laser, molecular resonance, thermal welding, and microdebrider.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PTH may have been reported as primary (generally defined as occurring within 24 hours of surgery), secondary (generally defined as occurring more than 24 hours postoperatively), or at an undefined or unspecified time. 8–108 Seventy-three studies contributed data to the meta-analysis (66 RCTs, 19,20,23,25,27,29,33,34,36,3841,43,44,46,47,49,50,5259,6264,67,71,72,7479,8184,88–92,95,101–105,108–122 6 nonrandomized trials, 24,35,37,45,48,94 and 1 prospective cohort study 70 ). The resulting subset of studies included the following tonsillectomy techniques: cold dissection, electrocautery, coblation, harmonic scalpel, laser, molecular resonance, thermal welding, and microdebrider.…”
Section: Resultsmentioning
confidence: 99%
“…815,19,20,23,25,27,3341,4347,5059,6264,67,7079,8184,88,89,91,92,9498,101,102,106–108,177 The 6299 children across studies who were treated with total tonsillectomy experienced 265 episodes (4.2%) of PTH (Table 2). PTH ranged from parent-reported bleeding that did not require accessing clinical care to reoperation for hemostasis.…”
Section: Resultsmentioning
confidence: 99%
“…This difference might be explained at first by a different operation technique. It is known that tonsillectomy using the dissection technique is more painful than when the guillotine technique is used . Secondly, by differences in treatment regime at home (acetaminophen with codeine vs acetaminophen and diclofenac).…”
Section: Discussionmentioning
confidence: 99%
“…There are two surgical techniques to perform tonsillectomy: a dissection and a guillotine technique, with the latter being less painful and resulting in less peri‐ and postoperative hemorrhage . Recent research suggests that pain after (dissection) tonsillectomy is often inadequately treated .…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the degree postoperative pain relates in part to the surgical approach for tonsillectomy, for example, radiofrequency versus dissection versus guillotine versus microdebrider [33][34][35][36][37][38] with extensive use of electrocautery resulting in the most postoperative pain. A recent suggestion has been to perform partial tonsillectomy to reduce airway obstruction while avoiding complete tonsillectomy and thus significantly reducing postoperative pain and therefore reducing the need for postoperative opioids [36,39].…”
Section: Surgical Considerationsmentioning
confidence: 99%